cAMP Bursts Control T Cell Directionality by Actomyosin Cytoskeleton Remodeling - Simao, Morgane; Régnier, Fabienne; Taheraly, Sarah; Fraisse, Achille; Tacine, Rachida; Fraudeau, Marie; Benabid, Adam; Feuillet, Vincent; Lambert, Mireille; Delon, Jérôme; Randriamampita, Clotilde (Frontiers in Cell and Developmental Biology, 2021)
T lymphocyte migration is an essential step to mounting an efficient immune response. The rapid and random motility of these cells which favors their sentinel role is conditioned by chemokines as well as by the physical environment. Morphological changes, underlaid by dynamic actin cytoskeleton remodeling, are observed throughout migration but especially when the cell modifies its trajectory. However, the signaling cascade regulating the directional changes remains largely unknown. Using dynamic cell imaging, we investigated in this paper the signaling pathways involved in T cell directionality. We monitored cyclic adenosine 3’-5’ monosphosphate (cAMP) variation concomitantly with actomyosin distribution upon T lymphocyte migration and highlighted the fact that spontaneous bursts in cAMP starting from the leading edge, are sufficient to promote actomyosin redistribution triggering trajectory modification. Although cAMP is commonly considered as an immunosuppressive factor, our results suggest that, conversely, when transient, it favors the exploratory behavior of T cells.